Investigation of the conditions forming the operational characteristics of the friction wedge of the vibration damper (Международный научный журнал «Инженер», 2026)
The article explores the prospects of using new materials for the production of friction wedges invibration dampers for freight car bogies, taking into account the design requirements. Research has beenconducted on reducing harmful impurities in the composition of cast iron and improving its strengthcharacteristics. The article considers various options for the mass fraction of elements in the cast ironcomposition, depending on the type of cast iron, and provides approximate data on hardness (HV) on thewalls of castings with different cross-sections. The reliability of the friction wedge vibration damper(FWVD) has a significant impact on the service life of rolling stock, as the friction force created todampen vertical and horizontal oscillations of the wagon body decreases over time due to the wear of theworking surfaces of the friction wedge. The friction wedge is a rapidly wearing component: the averagemileage of grey cast iron friction wedges before replacement is about 100,000 kilometers. The annualdemand for FWVDs, solely for depot repairs, exceeds 100,000 units. During the wear process,approximately 0.3 thousand tons of cast iron are irreversibly lost. Key research areas include optimizingthe chemical composition, enhancing the physicomechanical and tribological properties, as well asmathematical modeling of FWVD performance under various operating conditions and predicting theirbehavior in service.